Peranan Telemedicine Pada Penatalaksanaan Penyakit Jantung Koroner Akut - Omar, Hamed (ARKAVI [Arsip Kardiovaskular Indonesia), 2017)
The role of telemedicine in reducing morbidity, mortality and Coronary heart  disease has proven on a few qualified research, both in developing countries and in developed countries. by uploading electrocardiograph while coronary attack, like Acute myocardial Infarction to central data in the hospital, the patient or family can be quickly directed to the emergency room and at the same time operators, nurses and doctors at the hospital have prepared therapy and plans further medical help. Keywords: Telemedicine, Interval of intervention, Thrombolysis, Myocardial Infarction